Literature Review : Faktor Risiko Kejadian Diare Pada Balita Di Indonesia - Andika Agus Iryanto; Tri Joko; Mursid Raharjo (Jurnal Kesehatan Lingkungan, 2021)
Diarrhea is the excretion of faeces with an increasing frequency (three times a day) with a change in the consistency of the stool to become soft or watery, with or without blood / mucus in the stool. in 2019, there were 4,485,513 cases of diarrhea in Indonesia with diarrhea services for children under five by 40%. The purpose of this study was to provide information about risk factors for the incidence of diarrhea in children under five based on review studies. This research method is a literature review using the Sinta database as a reference. Categorization is done, index 2-4, publications in the last 10 years, and has variables related to risk factors for the incidence of diarrhea in children under five. The results of this study were found that environmental factors such as clean water facilities, latrine facilities, household waste management, liquid waste management, maternal knowledge, and personal hygiene are risk factors that cause diarrhea in toddlers. The conclusion of this research is that there are factors of poor sanitation, maternal knowledge, and personal hygiene which are risk factors for the incidence of diarrhea in toddlers that must be corrected.